Most efficient channel section with multiple slender obstructions in flow path - Singh S.M.; Maiti P.R. (My University, 2025)
An open channel is to be considered most efficient when it can pass maximum discharge for a given cross-sectional area, bottom slope and resistance of flow in the side walls. In the present work, the efficiency of channel section is determined analytically for rectangular and trapezoidal cross-section with slender structure equally spaced along the width of channel cross-section. The economic depth of flow and hydraulic radius is found for a given discharge with multiple barriers in flow path. The energy of flow is determined with slender structure in rectangular channel section. The proposed analytical solution will be helpful to optimum design of the lined rectangular and trapezoidal channel section with number of barriers that may be pier like structures. Copyright © 2021 Inderscience Enterprises Ltd.